2018
DOI: 10.1017/s0033291718002301
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of suicide attempt in individuals with major depressive disorder: a meta-analysis of observational surveys

Abstract: This meta-analysis confirmed that SA was common in individuals with MDD across the world. Careful screening and appropriate interventions should be implemented for SA in the MDD population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
82
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(97 citation statements)
references
References 127 publications
3
82
1
1
Order By: Relevance
“…Meta‐analysis has confirmed that suicide attempts are common among individuals with major depressive disorder around the world . Likewise, depressive disorder was, as expected, significantly related to suicide attempts when depressive symptoms worsened in our study.…”
Section: Discussionsupporting
confidence: 89%
“…Meta‐analysis has confirmed that suicide attempts are common among individuals with major depressive disorder around the world . Likewise, depressive disorder was, as expected, significantly related to suicide attempts when depressive symptoms worsened in our study.…”
Section: Discussionsupporting
confidence: 89%
“…The assessment of suicidality is an integral part of the evaluation of a patient with a diagnosis of depression, both in research and in clinical settings. A meta-analysis of 57 studies of more than 23,000 patients with depression found a lifetime rate of suicide attempt of 31% 42 . Suicidal ideation and suicide attempts are among the strongest predictors of completed suicide 43 , although the positive predictive value of any risk factor or risk algorithm is not high.…”
Section: Symptom Profilementioning
confidence: 99%
“…Prevalence of suicidal ideation (62.4%) and suicide attempt within a month (35.4%) that were found were higher than past studies in Asia. Rates of suicidal ideation reported in China [25,26] and Singapore [27] ranged from 49-55% among MDD patients and a recent meta-analysis showed a 24% 1-month prevalence of Chinese MDD patients having suicide attempts [28]. The variation of the prevalence may be influenced by the different tools using to evaluate suicidality.…”
Section: Resultsmentioning
confidence: 99%
“…1) The Beck Depression Inventory-II (BDI-II) Thai version, a widely used questionnaire for assessment of the severity of depression, was developed from its original version in English [18] and consists of 21 questions with a total score of 63. The severities of depression were categorized into minimal (0-13), mild (14)(15)(16)(17)(18)(19), moderate (20)(21)(22)(23)(24)(25)(26)(27)(28) and severe depression . The test showed good internal consistency (Cronbach's alpha coefficient, α = 0.91) and the Spearman's correlation coefficient, which indicated the relationship between the score obtained from this BDI-II and the Hamilton Rating Scale for Depression, was 0.71.…”
Section: Assessmentmentioning
confidence: 99%